Report and proceedings - Mc Intosh, Sarah (CRFM Secretariat [Belize City]BZ, 2009)
Provides information on fisheries initiatives in the region. Reviews previous activities of the Regional Fisherfolk Organisation Coordinating Unit (RFO-CU) and makes suggestions for the preparation of strategic and action plans, including a communication strategy and plan for the RFO-CU.